1995
DOI: 10.1152/ajpheart.1995.268.1.h39
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of nitric oxide to coronary vasodilation during hypercapnic acidosis

Abstract: The present study was performed to evaluate the role of nitric oxide (NO) in coronary vasodilation during hypercapnic acidosis (HC). The left anterior descending coronary arteries of 17 anesthetized, open-chest dogs were perfused with normal arterial blood or with arterial blood equilibrated in an extracorporeal circuit with 90% O2-10% CO2 [arterial carbon dioxide tension (PaCO2) 72 +/- 3 mmHg, arterial pH 7.16 +/- 0.02]. Coronary perfusion pressure (CPP) was initially set at 100 mmHg. Coronary blood flow (CBF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 0 publications
4
49
0
1
Order By: Relevance
“…The importance of the endothelium for the vasodilatory e ect of CO 2 has been demonstrated in the cerebral and coronary circulations (Fabricius & Lauritzen, 1994;Gurevicius et al, 1995). Therefore, we investigated the signi®cance of the endothelium on the hypercapnia-produced relaxation in the mesenteric vascular bed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the endothelium for the vasodilatory e ect of CO 2 has been demonstrated in the cerebral and coronary circulations (Fabricius & Lauritzen, 1994;Gurevicius et al, 1995). Therefore, we investigated the signi®cance of the endothelium on the hypercapnia-produced relaxation in the mesenteric vascular bed.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of nitric oxide synthase (NOS) attenuates the increase in the cerebral blood¯ow and coronary blood¯ow elicited by hypercapnia (Fabricius & Lauritzen, 1994;Gurevicius et al, 1995). Hsu et al (1995) also demonstrated that hypercapnia stimulates synthesis of vasodilatory prostanoid(s) in cerebral vascular endothelial cells but not in vascular smooth muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty minutes later, the bath solution was returned to control conditions. The response of a preparation to the intervention in these experiments was quantified as the difference between the average tension during minutes [15][16][17][18][19][20] after the switch to experimental conditions and the average steadystate control tension during the last 5 min before the switch. We took samples of the bathing fluid throughout all the experiments for the analysis of PCO2 and pH by using an automated blood-gas analyzer (model 278, Ciba Corning).…”
Section: Methodsmentioning
confidence: 99%
“…NO was proposed as a mediator of hypercapnia-evoked coronary vasodilation in the in situ dog heart (20) and findings in isolated aortic strips suggest that vasorelaxation in this artery in response to CO 2 may be partially mediated by NO (21). A number of publications have implicated NO in the vasodilatory response of the cerebral vasculature to hypercapnia (22), although more recent evidence suggests that the role of NO may be "permissive" rather than "causative" in this vascular bed (23).…”
Section: Respiratory Acidosismentioning
confidence: 99%